2013
DOI: 10.4191/kcers.2013.50.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Duty Cycle on the Characteristics of Al2O3Coatings Formed on the Al-1050 by Plasma Electrolytic Oxidation

Abstract: Oxide coatings were prepared on Al-1050 substrates by an environment-friendly plasma electrolytic oxidation (PEO) process using an electrolytic solution of Na 2 SiO 3 (8 g/L) and NaOH (3 g/L). The effects of three different duty cycles (20%, 40%, and 60%) and frequencies (50 Hz, 200 Hz, and 800 Hz) on the structure and micro-hardness of the oxide coatings were investigated. XRD analysis revealed that the oxides were mainly composed of α-Al 2 O 3 , γ-Al 2 O 3 , and mullite. The proportion of each crystalline ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…of the coatings. 9) The studies reported thus far on NbN coatings are primarily on the use of dc sputtering method, most of which involve variations in the amount of flown-in nitrogen, the substrate temperature and the deposition time as coating process variables. [10][11][12] In particular, no study results of quantitative analysis and consideration have been reported for the effects of plasma process variables such as duty cycle and pulse frequency using the asymmetric bipolar pulse sputtering method on crystal structure, surface and cross section microstructure, grain size, etc.…”
Section: Introductionmentioning
confidence: 99%
“…of the coatings. 9) The studies reported thus far on NbN coatings are primarily on the use of dc sputtering method, most of which involve variations in the amount of flown-in nitrogen, the substrate temperature and the deposition time as coating process variables. [10][11][12] In particular, no study results of quantitative analysis and consideration have been reported for the effects of plasma process variables such as duty cycle and pulse frequency using the asymmetric bipolar pulse sputtering method on crystal structure, surface and cross section microstructure, grain size, etc.…”
Section: Introductionmentioning
confidence: 99%